Pengaruh Kualitas Pelayanan, Harga, Kepercayaan dan Kepuasan terhadap Loyalitas Konsumen Maxim di Kota Samarinda - Sailawati; Tjetje, Noor Fachman; Fitri Andriani (Politeknik Negeri Samarinda, 2024)
This study aims to determine the Effect of Service Quality, Price, Trust and Satisfaction on Maxim Customer Loyalty in Samarinda City. This study used a quantitative approach, using primary data through questionnaires. The respondents in this study were Maxim users in Samarinda City with qualifications who had used Maxim transportation services. The independent variables used in this study were Service Quality, Price, Trust and Satisfaction. While the dependent variable in this study is Consumer Loyalty. In this study, the analysis tool used was multiple linear regression with the help of Statistical Product and Services Solutions (SPSS) software version 20. This study used multiple linear regression analysis with the equation. The results showed that service quality, price and satisfaction had a positive and significant effect on consumer loyalty. While trust has no effect and is not significant on consumer loyalty. Then it can be concluded that H1, H2 and H4 are accepted while for H3 are rejected. The results also showed that service quality, price, trust and satisfaction simultaneously have a positive and significant influence on the loyalty of Maxim customers in Samarinda City.